2015
DOI: 10.1136/vr.h5934
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotics in animals and people

Abstract: questions whether further restrictions on veterinary antibiotic use are required in the UK (VR, September 19, 2015, vol 177, pp 292-293) and, in support of his case, quotes statistics showing that farm antibiotic use per total population correction unit (PCU) in the UK is already significantly lower than in the Netherlands and nearly as low as in Denmark. However, the European Medicines agency (EMa), which publishes annual veterinary antibiotic sales data for European countries, and introduced the PCU unit for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The different monitoring systems for the use of antibiotics in animals and the surveillance of resistance to antibiotics were established in European countries (BTK 2015;Borck Høg et al 2017; SDa Autoriteit Diergenesmiddelen 2018; SWEDRES/SVARM 2018; MARAN 2019). In 2015, Nunan and Young (2015) reported that antibiotics, particularly colistin, should not be routinely used as prophylactics in animal farms in the United Kingdom (UK). The authors added that colistin accounted for only 0.2% of all antibiotics that were used in breeding in the UK and was only used by veterinarians to treat sick animals (EMA/CVMP 2010; Nunan and Young 2015;Catry et al 2015).…”
Section: Colistin In Veterinary Medicine and Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…The different monitoring systems for the use of antibiotics in animals and the surveillance of resistance to antibiotics were established in European countries (BTK 2015;Borck Høg et al 2017; SDa Autoriteit Diergenesmiddelen 2018; SWEDRES/SVARM 2018; MARAN 2019). In 2015, Nunan and Young (2015) reported that antibiotics, particularly colistin, should not be routinely used as prophylactics in animal farms in the United Kingdom (UK). The authors added that colistin accounted for only 0.2% of all antibiotics that were used in breeding in the UK and was only used by veterinarians to treat sick animals (EMA/CVMP 2010; Nunan and Young 2015;Catry et al 2015).…”
Section: Colistin In Veterinary Medicine and Agriculturementioning
confidence: 99%
“…In 2015, Nunan and Young (2015) reported that antibiotics, particularly colistin, should not be routinely used as prophylactics in animal farms in the United Kingdom (UK). The authors added that colistin accounted for only 0.2% of all antibiotics that were used in breeding in the UK and was only used by veterinarians to treat sick animals (EMA/CVMP 2010; Nunan and Young 2015;Catry et al 2015).…”
Section: Colistin In Veterinary Medicine and Agriculturementioning
confidence: 99%
“…Breeding with research and development, execution of practical tests, optimization, record and approval by regulatory organizations from each country or block for a new drug may take 20 years. That investment is high and the private sector eventually restricts the production and research according to the obtained financial return, that is, the offer of medicines may be influenced by adverse factors that go beyond the demand and needs regarding the animals, especially concerning highly technical medicines and with a limited or restricted distribution flow in the market [10,11].…”
Section: Challengesmentioning
confidence: 99%